Governance Mechanism As Driver Of Performance Mediated By Reputation – A Study Of Charity Foundations For People With Disabilities In Malaysia - Yew, Rebecca Ming Yian (2020)
Charity foundations (CFs) are philanthropic institutions set up to render welfare programmes for the societal welfare of the public and environment. Generally, stakeholders have an impression that CFs are providing not as much accountability contrasted from the corporate organizations (COs), therefore, governance is taking a significant value of benevolence management since certain CFs have under gone media observation because of scandals and wrongdoings on how they carry out their charitable objectives. This study is carried out with the purpose of examining governance mechanism through the board of trustees (BOT) mediated by reputation on the performance of CFs for people with disabilities in Malaysia. A framework was formed using three major theories – Stakeholders, Resource Dependence and Stewardship which served as the foundation of this study. Primary data was gathered from 252 CFs for people with disabilities (OKU) which were provided by Registry of Society Malaysia (ROS). A total of 73 questionnaire were returned which accounted for 28.97% of total sample size. Partial least square structural equation modeling (PLS-SEM) was employed as main statistical technique in this study. The results from the analysis and tests indicated that out of seven hypotheses developed in this study, four hypotheses were supported with significant relationships. Besides, the findings of the study indicated that reputation being the mediator had significant mediation effect on the independent constructs (function and accountability) to influence the dependent construct (performance). Therefore, OKU CFs must escalate their current accountability practice and present their foundations in a positive light through reputation since reputation is the cornerstone of OKU CFs differentiation strategy. Moreover, through reputation, donors and external stakeholders can be influenced to voluntarily contribute resources to support the charity to ensure their survival into the future. Despite board function did not have direct significant effect on charity performance, however, through charity reputation the relationship became significant which implies that charity ought to work towards board function to create a good image and reputation for the benefit of the institution overall.